2014
DOI: 10.1016/j.neuroimage.2014.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Obesity gene NEGR1 associated with white matter integrity in healthy young adults

Abstract: Obesity is a crucial public health issue in developed countries, with implications for cardiovascular and brain health as we age. A number of commonly-carried genetic variants are associated with obesity. Here we aim to see whether variants in obesity-associated genes - NEGR1, FTO, MTCH2, MC4R, LRRN6C, MAP2K5, FAIM2, SEC16B, ETV5, BDNF-AS, ATXN2L, ATP2A1, KCTD15, and TNN13K - are associated with white matter microstructural properties, assessed by high angular resolution diffusion imaging (HARDI) in young heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…However, declines in nodal and paranodal axonal complexes observed in HFD mice indicate that axonal conduction could be impaired. Single nucleotide polymorphisms in the neuronal cell adhesion gene, Negr1, are associated with obesity (Willer et al, 2009) and reduce FA in white matter tracts (Dennis et al, 2014) suggesting that there may also be neuronal factors driving reduced axoglial signaling and myelination in obese white matter.…”
Section: The Structural Integrity Of White Matter Is Compromised By Omentioning
confidence: 99%
“…However, declines in nodal and paranodal axonal complexes observed in HFD mice indicate that axonal conduction could be impaired. Single nucleotide polymorphisms in the neuronal cell adhesion gene, Negr1, are associated with obesity (Willer et al, 2009) and reduce FA in white matter tracts (Dennis et al, 2014) suggesting that there may also be neuronal factors driving reduced axoglial signaling and myelination in obese white matter.…”
Section: The Structural Integrity Of White Matter Is Compromised By Omentioning
confidence: 99%
“…The corona radiata is an extensive WM structure with large fibres carrying information from and to the cerebral cortex. Interestingly, a recent study investigating the effect of 16 obesity‐related genes in mostly normal‐weight young adults showed the strongest association between the obesity‐risk gene neural growth regulator 1 ( NEGR1; rs2815752 ) and lower WM integrity (lower FA values), especially in the corona radiata . NEGR1 is important for neural development and the risk allele has been associated with a higher BMI .…”
Section: Dti Studies In Obesity Researchmentioning
confidence: 99%
“…Overlap between genetic risk for obesity and white matter microstructural integrity (in the corpus callosum and superior fronto-occipital tract) has also been reported (Spieker et al, 2015). SNPs in a number of candidate genes, including FTO (Chuang et al, 2015), and NEGR1 (Dennis et al, 2014) have also been shown to contribute to both obesity and neural structure and/or function.…”
mentioning
confidence: 99%